TECHNOLOGICAL TRANSFORMATIONS OF THE AGRICULTURAL SECTOR NATIONAL ECONOMY IN THE CONTEXT OF THE TRANSITION TO SMART TECHNOLOGIES - Гавкалова, Наталія Л. (Journal of Strategic Economic Research, 2024)
The article examines the directions of transformation of the agro-industrial sector of the national economy based on the implementation of modern smart technologies. It was found that with the development of new technologies, more and more agricultural production processes are moving from manual to automated work. This is facilitated by the invention of smart technologies, which are understood as a new management strategy due to the digital characteristics of processes. Smart technologies in agriculture are called agritech. It was determined that the following smart technologies are being implemented at the level of the agro-industrial sector: the Internet of Things – a smart technology that allows various devices to exchange data with each other without human intervention; robotics – smart technology, with the help of which unmanned tractors and "harvesting hands" are created; artificial intelligence – smart technology for synchronization of agricultural equipment, data analysis, decision-making and application of optimal actions at all stages of agricultural production; agricultural drones – unmanned aerial devices for monitoring the condition of crops; yield estimates; water shortage assessments; detection of weeds, etc.; precision agriculture – a smart agricultural management technology that combines modern data collection and communication technologies; agricultural biotechnologies – smart technologies used to improve plants, animals and microorganisms; big data and its analysis – smart technologies used to increase the accuracy of forecasting and increase the efficiency of the agro-industrial sector; controlled agriculture – smart technologies for growing agricultural crops in a controlled environment; renewable agriculture – smart technologies for creating renewable food systems and healthy natural ecosystems; connection technologies – smart technologies of using digital programs and analytics based on 5G technologies. It has been proven that the introduction of smart technologies in the agro-industrial sector contributes to the activation of the production of agricultural products and increases the number of people who can be provided with food from 1 acre of land to 265 people. Therefore, the gradual technological transformation of the agro-industrial sector of Ukraine on the basis of the transition to smart technologies will contribute to the expansion of the scale, speed and productivity of agricultural equipment, increasing the efficiency of land cultivation with fewer people, increasing the volume of agricultural production and increasing its yield.